(3OjhGf dSGf GdOjf GHf GdNWjHs - (3CHh YHO Gddg dSGf GdOjf eMeO Hf YHO Gddg Hf SYjO GHf GdNWjH GdZQfGWi GdCfOdSj,J (B776 (3g` s
(3ChdgG (B:s
(3eHJhQ hjHJOF CKfGA bGajI GdgeRI(B: (3SjOj CeOM YeOJj aGMJedfj HeJdi CfJ HGdHQGHQ hGdZR R, hCgd GdLHGd hGdUMQGA s
(3BNQgG (B:s
(3eHJhQ hjfJgj CKfGA bGajI GdQGA ef bUjOI NGWH HgG bGFO GdHMQ CHG GdYHGS GHf GdNWjH Hbhdg(B: (3jGaGQS GdCLhGO Hfj Sajfg s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B235s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B188 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
(3GdfSNI HgG JdhjK s
Keywords: (3GdCOHs